The Analysis of Construction Supply Chain Management Failure - Amir Anwar; Yenni Carolina (Conference Series, 2020)
A multisite construction project is a construction project characterized by the number of construction sites that are managed simultaneously in regional, national and even global coverage. In its implementation and completion, a multisite construction project has field problems with high complexity. This problem is generally caused by the distribution of work locations, relatively short execution times, weather, and access. One of the failure factors in multisite construction is suspected to be the result of the improper and unplanned implementation of SCM (supply chain management). This study aims to provide input to parties involved in multisite CSCM (supply chain management) construction regarding the importance of compiling a correct, precise and effective SCM in multisite construction. Data collection was carried out into three stages, namely literature study, interview and observation. Data from interviews and field observations are interpreted and processed in the NVivo12 application. Based on data processing, it is known that the factors that cause poor multisite CSCM from internal companies are corporate culture, availability of human resources, construction management, while external factors are factors of service users, the involvement of subcontractors, availability of reliable suppliers and work environment. These findings provide a reference for practitioners who use SCM in construction. Based on these findings, practitioners can pay attention to various factors that cause failure in implementing CSCM.